EVOLUTION OF THE NATURAL GROWTH AND THE ANALYSIS OF THE SEASONALITY OF LIVE BIRTHS AND DEATHS FROM ROMANIA AND BACAU COUNTY IN THE LAST FOUR YEARS - Harja, Eugenia; Stângaciu, Oana-Ancuţa (Studies and Scientific Researches. Economics Edition, 2014)
Since 1992, Romania's population declined every year naturally, the number of deaths being higher than live births. If in Bacau until 2002 we had to deal with natural growth of the population, even if increasingly less, starting that year it emerged more and more the process of decline of the population. In both cases, the phenomenon is more pronounced in rural areas than in urban areas due to more pronounced aging of the rural population. Both in the case of live births and deaths it is observed the seasonal oscillation by the months of the year. If in the case of births they are more numerous in the summer months and in decrease in the winter months, the situation is exactly the opposite in the case of deaths. Thus from here we have the natural decrease of the population, which increases in the winter months and starts to decline or become slightly positive in July-September.